2014
DOI: 10.1293/tox.27.1s
|View full text |Cite
|
Sign up to set email alerts
|

Nonproliferative and Proliferative Lesions of the Rat and Mouse Female Reproductive System

Abstract: The INHAND (International Harmonization of Nomenclature and Diagnostic Criteria for Lesions in Rats and Mice) Project (www.toxpath.org/inhand.asp) is a joint initiative of the Societies of Toxicological Pathology from Europe (ESTP), Great Britain (BSTP), Japan (JSTP) and North America (STP) to develop an internationally accepted nomenclature for proliferative and nonproliferative lesions in laboratory animals. The purpose of this publication is to provide a standardized nomenclature for classifying microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
180
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(197 citation statements)
references
References 164 publications
4
180
0
3
Order By: Relevance
“…It is noteworthy to mention that 10/23 endometrial neoplasms (adenomas and one adenocarcinoma) revealed focal decidualizations. Similar changes have been described in rats and mice, where these focal decidualizations occur in conjunction with polyps or other tumours or induced hormonal changes (Dixon et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is noteworthy to mention that 10/23 endometrial neoplasms (adenomas and one adenocarcinoma) revealed focal decidualizations. Similar changes have been described in rats and mice, where these focal decidualizations occur in conjunction with polyps or other tumours or induced hormonal changes (Dixon et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…Both are similar changes. In accordance with descriptions in the rat and mouse (Dixon et al, 2014), we referred to 'focal decidualization' when the lesions were part of another change (i.e. adenoma or adenocarcinoma) (Fig.…”
Section: Placental Lesionsmentioning
confidence: 80%
“…Judging from the histological nature and the mode of incidences, the other histologic changes than the above-mentioned ones were considered not to be specific for NOG mice (Kaufmann et al, 2012;Pearse, 2006b;Khosla and Ovalle, 1986;Hardisty andBoorma., 1999: Leininger et al, 1999;Creasy et al, 2012;Dixon et al, 2014;Long and Leininger, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone has been shown to inhibit uterine gland development in the neonatal mouse uterus (31,32), while estrogen seems to be required for maintaining uterine gland function in adult mice (33). Aged mice can spontaneously develop cystic endometrial hyperplasia (34), which involves dilation and proliferation of the glandular ducts. The glandular duct cysts vary in size but are restricted within the endometrium.…”
mentioning
confidence: 99%
“…Adenomyosis refers to the invasion of hyperplastic glands into the myometrium (35), which can be difficult to differentiate from endometriosis (36) when the dislocated endometrial tissue is still associated with the uterus. Hydrometra may also cause uterine horn dilation (34), which is, however, due to uterine horn lumenal distension without involving the uterine glands. Finally, uterine tumors with or without gland involvment can cause uterine horn dilation.…”
mentioning
confidence: 99%